2013
DOI: 10.1080/14703297.2013.796711
|View full text |Cite
|
Sign up to set email alerts
|

Using computer-based technology to improve feedback to staff and students on MCQ assessments

Abstract: The massification of higher education (HE) has led to an unprecedented increase in the number of students in the classrooms, resulting in increased workload for teaching staff, sometimes leading to a great reliance on Multiple Choice Questions (MCQs) examinations with limited feedback provided to students. The central role of feedback in student learning is well recognised; however, it is often one of the poorest scoring items in Student Evaluation of Teaching and Learning (SETL) surveys. Teaching staff also n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Evaluating the quality of questions has attracted significant interest in educational research. Standard metrics from classical test theory and item response theory, such as discrimination indices, have been used for decades to aid instructors in identifying poor quality questions (Brown et al 2021;Malau-Aduli et al 2014). However, computing such quantitative measures requires large quantities of data on student responses to items.…”
Section: Related Workmentioning
confidence: 99%
“…Evaluating the quality of questions has attracted significant interest in educational research. Standard metrics from classical test theory and item response theory, such as discrimination indices, have been used for decades to aid instructors in identifying poor quality questions (Brown et al 2021;Malau-Aduli et al 2014). However, computing such quantitative measures requires large quantities of data on student responses to items.…”
Section: Related Workmentioning
confidence: 99%
“…Butcher and Hoosen (2014) stated, "fundamental judgments about quality should not depend on whether education is provided in a traditional or post-traditional manner" He pointed that quality assurance of distance education should be similar to general education assurance in higher education. Bunmi S. et al (2014) indicated in their study entitled, Using Computer-based technology to improve feedback to staff and students on MCQ that students' responses, showed satisfaction of MCQ in terms of time comprehension revision, while teaching staff is satisfied with the efficient provision of automatic feedback about students' learning progress, which leads to quality assurance and support students learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teaching, research, and administrative workloads put pressure on the time available for course improvement . Many staff who are involved in designing, running, and administering laboratory teaching practicals have numerous demands on their time as they may also be active researchers and have additional school‐level and university‐level administrative duties.…”
Section: Presentation Of Datamentioning
confidence: 99%